Respuesta :
Answer:
[tex]1.\ 10+x+ 8 = 18+ x[/tex]
[tex]2.\ 9(3x) = 27x[/tex]
[tex]3.\ \frac{1}{2}(10x) + 7 - 3 = 5x + 4[/tex]
[tex]4.\ -5(4x) = -20x[/tex]
[tex]5.\ 10 - 2 (8x) - 3 = 7 - 16x[/tex]
[tex]6.\ 3(7x) + 3 (-5) = 21x -15[/tex]
Step-by-step explanation:
Required
Solve each expression
[tex]1.\ 10+x+ 8[/tex]
Start by collecting like terms
[tex]10+ 8+x[/tex]
Add like terms
[tex]18+x[/tex]
The expression can't be solved further
Hence; [tex]10+x+ 8 = 18+ x[/tex]
[tex]2.\ 9(3x)[/tex]
Open the bracket
[tex]9 * 3x[/tex]
[tex]27x[/tex]
The expression can't be solved further
Hence, [tex]9(3x) = 27x[/tex]
[tex]3.\ \frac{1}{2}(10x) + 7 - 3[/tex]
Open bracket
[tex]\frac{1}{2} * 10x + 7 - 3[/tex]
[tex]5x + 7 - 3[/tex]
[tex]5x + 4[/tex]
The expression can't be solved further;
Hence, [tex]\frac{1}{2}(10x) + 7 - 3 = 5x + 4[/tex]
[tex]4.\ -5(4x)[/tex]
Open the bracket
[tex]-5 * 4x[/tex]
[tex]-20x[/tex]
The expression can't be solved further
Hence, [tex]-5(4x) = -20x[/tex]
[tex]5.\ 10 - 2 (8x) - 3[/tex]
Open Bracket
[tex]10 - 2 *8x - 3[/tex]
[tex]10 - 16x - 3[/tex]
Collect like terms
[tex]10 - 3 - 16x[/tex]
[tex]7 - 16x[/tex]
The expression can't be solved further
Hence, [tex]10 - 2 (8x) - 3 = 7 - 16x[/tex]
[tex]6.\ 3(7x) + 3 (-5)[/tex]
Open both brackets
[tex]3*7x + 3 * -5[/tex]
[tex]21x -15[/tex]
The expression can't be solved further
Hence, [tex]3(7x) + 3 (-5) = 21x -15[/tex]